Level of academic and didactic competencies among students as a measure to evaluate geographical education and preparation of students for the demands of the modern labour market - Cichoń, Małgorzata; Piotrowska, Iwona (Quaestiones Geographicae, 2019)
Young people, regardless of their social environment, place of residence or work, are looking for values and key competencies that enable achieving goals in life. Therefore, an appropriate education system is important, which in the conditions of changing reality will meet these requirements effectively. The contemporary employer is interested in four groups of key competencies, such as intellectual, professional, personal and interpersonal. Geography is a field with great potential for the development of various competencies. In this context, questions about adjusting geographical education to the expectations of employers are justified. Therefore, the aim of the study is to assess the strengths and weaknesses of the current development of competencies and qualifications at the geography speciality of the Faculty of Geographical and Geological Sciences, Adam Mickiewicz University in Poznań, Poland. The reference points included a report on research carried out among 200 employers in 2012, as well as surveys among students graduating from master‘s studies on the assessment of the level of their competencies and qualifications. It was determined that the strength of the current geographical education at the faculty is to prepare mainly specialists with broad general and professional knowledge, and high self-esteem in terms of cooperation in the group and communication. The area of development for the geographical education are intellectual competencies, above all independent thinking and prioritising. The last year geography students fall out the most in terms of personal competencies. The authors suggest building students‘ awareness because, as the above results show, they are not fully aware of what expectations they may face in the labour market. It is worth modifying the study program so as to put more emphasis on soft competencies and support the development of various forms of extra activities of students. Attention was also paid to the importance of didactic competencies, which on the one hand raise the self-esteem of students, and on the other, increase the chance of finding a good job. An interesting aspect of the research is the wide spectrum of professions in which students work. This reflects their diverse skills, including spatial thinking. Combined with increasing attention paid to the issues related to the natural environment and sustainable development, graduates of geography have a strong position to enter the current labour market. The advantage of geographers is the use of modern technologies. Unfortunately, however, the results of the research presented above, both among Polish students and internationally, indicate insufficient skills in the use of modern technologies by students of geography.